2011
DOI: 10.1021/ja2056227
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing Mesoporous Carbon Thin Films with Highly Ordered Pore Architectures for Nanodevices

Abstract: We report for the first time the synthesis of free-standing mesoporous carbon films with highly ordered pore architecture by a simple coating-etching approach, which have an intact morphology with variable sizes as large as several square centimeters and a controllable thickness of 90 nm to ∼3 μm. The mesoporous carbon films were first synthesized by coating a resol precursors/Pluronic copolymer solution on a preoxidized silicon wafer and forming highly ordered polymeric mesostructures based on organic-organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(182 citation statements)
references
References 39 publications
2
178
2
Order By: Relevance
“…For comparison, free standing OMC thin fi lm based supercapacitor, without attaching 3D-graphene foam, was assembled according to the previous literature. [ 41 ] Copper wires were embedded and connected to carbon materials with silver paste, which enables a strong electrical contact and a small contact resistance between the copper wires and the active materials. The electrolyte used in all of the measurements was a 6 M KOH or 1 M H 2 SO 4 aqueous solution, which was sealed by adhesive tape.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, free standing OMC thin fi lm based supercapacitor, without attaching 3D-graphene foam, was assembled according to the previous literature. [ 41 ] Copper wires were embedded and connected to carbon materials with silver paste, which enables a strong electrical contact and a small contact resistance between the copper wires and the active materials. The electrolyte used in all of the measurements was a 6 M KOH or 1 M H 2 SO 4 aqueous solution, which was sealed by adhesive tape.…”
Section: Methodsmentioning
confidence: 99%
“…Various shapes and morphologies of mesoporous carbons, such as single crystals [20], monoliths [21], fibers [21], nanospheres [22], vesicles [23]. and films [24] have been synthesized.…”
Section: Synthesis and Characterization Of Omcmentioning
confidence: 99%
“…It has been shown that the electron transfer resistance of OMC is much lower than that on CNT [24] suggesting that OMC can form good electron pathway between the electrode and electrolyte. Recent works showed that the apparent electrode area is about 0.063 cm 2 [31] higher than that of CNT.…”
Section: Electrochemical Properties Of Omcmentioning
confidence: 99%
“…Alternatively, to introduce the desired roughness for superhydrophobicity on surfaces and conductivity in polymers, carbon based nanoparticle techniques may be another approach. Mesoporous carbon nanoparticles, which are a class of semi-crystalline or glassy carbon based materials, have attracted great interest due to their outstanding properties, such as their high specific surface area, ordered mesostructure, tunable pore size, low density, good conductivity and chemical stability, which are all of great significance in a wide range of applications [18][19][20][21]. However, carbon based superhydrophobic films have not yet been developed for multifunctional/smart applications that could require the encapsulation/release of functional nanomaterials.…”
Section: Introductionmentioning
confidence: 99%